The Influence of Access Barriers on Outpatient Services Use among Low-income Households in Malaysia. - Aziz Jamal; Yunfei Li; Ning Liu; Mohd Zulkifli Abdullah (Asia Pacific Journal of Health Management)
Aim: Many people, particularly those from low-income and marginalised communities, face barriers when accessing healthcare services. Therefore, this study examined the influence of household characteristics and perceived access barriers on the utilisation of outpatient services among low-income households living in urban and rural areas.